The Role of Digital Payment Adoption (QRIS) and Financial Inclusion in Enhancing the Financial Performance of Micro Enterprises in Cirebon City - Meiydida Arfansyah Pasaribu; Nurhana Dhea Parlina (Journal of Business, Social and Technology, 2026)
Background: MSMEs contribute significantly to Indonesia’s economy, yet many still face limited financial access and low digital literacy. QRIS was introduced to support digital payments and financial inclusion, but its impact on MSME financial performance remains unclear. Objective: This study seeks to examine how financial inclusion and digital payment adoption (QRIS) may enhance the financial performance of microenterprises in Cirebon City. The phenomena of economic digitization and the relevance of financial access to MSME sustainability form the basis of this study. Methods: This study employed a survey technique in conjunction with a quantitative approach. Microenterprise owners in Cirebon City's culinary industry constituted the study population, and the Slovin formula was used to calculate the sample size of 94 respondents. Questionnaires were used for data collection, and SPSS was utilized for multiple linear regression analysis. Results: The study's findings indicate that: (1) financial performance is positively and significantly affected by the adoption of digital payments (QRIS), as demonstrated by a t-statistic of 6.811 and a significance value of 0.000; (2) financial inclusion has a positive and significant impact on financial performance, as demonstrated by a t-statistic of 5.711 and a significance value of 0.000; and (3) both variables simultaneously exert a significant effect, with an F-statistic of 28.798. Together, the two variables explain 38.8% of the variance in financial performance. Conclusion: The study highlights the critical role of equitable financial access and the implementation of payment technologies in promoting the growth and financial performance of microenterprises.